IoT-based Pico-Hydro Power Generation System Using Pelton Turbine - Fortaleza, Benedicto N.; Juan, Ronnie O. Serfa; Tolentino, Lean Karlo S. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The local rural electric power generation is necessary to promote progress of the localities especially on those hard to reach communities. The Philippine archipelago is rich in water resources, harnessing this ample amount of water is enough for irrigation and electrical generation especially on those far located areas that are hard to reach by electrical grid connection system. This paper presents an alternative source of electrical energy. The designed pico-hydro power generation system is well suited in remote areas where the transmission of power seems to impossible. To maximize the designed concept, the Pelton turbine is utilized because it is suited especially in the Philippines for high and low flow rate of water. Moreover, an IoT-based system that can easily monitor any unwanted problems. This pico-hydropower system is much economical compared with other sources of electricity.